Enhancement of Cellulase Production in Trichoderma reesei via Disruption of Multiple Protease Genes Identified by Comparative Secretomics - Qian, Yuanchao; Zhong, Lixia; Sun, Yu; Sun, Ningning; Zhang, Lei; Liu, Weifeng; Qu, Yinbo; Zhong, Yaohua (Frontiers in Microbiology, 2019)
The filamentous fungus Trichoderma reesei is one of the most studied cellulolytic organisms and the major producer of cellulases for industrial applications. However, undesired degradation of cellulases often happens in culture filtrates and commercial enzyme preparations. Even studies have been reported about describing proteolytic degradation of heterologous proteins in T. reesei, there are few systematic explorations concerning the extracellular proteases responsible for degradation of cellulases. In this study, the cellulase activity was observed to rapidly decrease at late cultivation stages in T. reesei. It was discovered that this decrease may be caused by proteases. To identify the proteases, comparative secretomics was performed to analyze the concomitant proteases during the cellulase production. 12 candidate proteases from the secretome of T. reesei were identified and their encoding genes were individually deleted via homologous recombination. Furthermore, three target proteases (tre81070, tre120998 and tre123244) were simultaneously deleted by one-step genetic transformation. The triple deletion strain ΔP70 showed a 78% decrease in protease activity and a 6-fold increase in cellulase activity at the late stage of fermentation. These results demonstrated the feasibility of improvement of cellulase production by genetically disrupting the potential protease genes to construct the T. reesei strains with low extracellular protease secretion. This dataset also provides an efficient approach for strain improvement by precise genetic engineering combined with “omics” strategy for high-production of industrial enzymes to reduce the cost of lignocellulose bioconversion.